THE EFFECT OF JOB INSECURITY, WORK STRESS, AND ROLE CONFLICTS ON TURNOVER INTENTIONS IN EMPLOYEES - Dhia Malihah, Fadhila; C. Catur Widayati; L. Atika Novianty (Dinasti Publisher, 2022)
This study was to determine the effect of Job Insecurity, Work Stress and Role Conflict on Turnover Intention in employees. The object of this research is accounting employees who work at PT Optik. The study was conducted on 58 respondents using a quantitative descriptive approach. The approach used in this study is the Variance Based Structural Equation Model (SEM) with Smart-PLS analysis tools. The results of this study showed that job insecurity variables have a significant positive effect on turnover intention, work stress has a significant positive effect on turnover intentions, and conflicts. The role of a significant positive influence on turnover intention.